Level Glukosa Darah pada Mencit Diabetes Setelah Pemberian Ekstrak Rumput Laut Coklat (Phaeophyta) - Mega Bintang Bella Pertiwi; Didin Erma Indahyani; Depi Praharani (UPT Percetakan dan Penerbitan Universitas Jember, 2021)
Diabetes mellitus (DM) is a disorder of hyperglycemia and glucose intolerance caused by insulin deficiency or insulin disorder. Insulin hormone functions in the formation of glucose as an energy source. Consequently, glucose accumulates in the blood in DM patients and affects increased free radicals within the cell and oxidative stress. In DM patients with an imbalance of oxidants and antioxidants in his plasm, therefore, patients with DM require a large amount of antioxidants intake. One alternative treatment is seaweed. Brown seaweed contains bioactive components such as polyphenols and carotenoids, which exhibit antioxidants and reduce blood glucose levels. The study aimed to analyze the effect of brown seaweed extract on the blood glucose levels in diabetic mice. The study used a research design of pre and post-test control group design. The study was divided into 4 sample groups, namely the normal group, negative controls (diabetic mice), positive control (diabetic mice + 1.3 mg / 20 gr BB metformin), P1 (diabetic mice + brown seaweed extract). The seaweed dose of 10mg / 20grBB is given daily for 21 days. Blood glucose level checks using Glucometer and strip test (Autocheck™). Brown seaweed extract has an effect on reducing blood glucose levels in diabetic mice.